SHIFTING PHENOMENON: AN ANALYSIS OF STAND UP COMEDY INDONESIA - Sihombing, Lambok Hermanto; Aninda, Maria Paskalia (Universitas Mercu Buana, 2023)
The lengthy road of Stand Up Comedy Indonesia has not been in vain, as it has become a popular event with many followers. Stand-Up comedy is today well-known not only due to the excitement of the show but also because the content delivered is of excellent quality and suited for all audiences. However, many comedians whose careers were launched by Stand-Up Comedy have since changed careers. This is, of course, a topic worthy of further investigation. This study tries to analyze the growth of stand-up comedy in Indonesia by examining the paths of comedians who left their comfort zones for new careers. To solve the research topic, the primary issue is the path of a former stand-up comedian who now works in a different field. Consequently, this study combines descriptive qualitative methodologies with various data acquired via content analysis on social media platforms such as YouTube, TikTok, and Instagram. According to Raskin (1985), psychological theory predominantly analyses comedy. Hence humour theories from a psychological perspective are highly developed. This study demonstrates that ups and downs have marked the long journey of Stand Up Comedy Indo until it has become popular and well-liked by the people of Indonesia. On the other hand, the author discovers that at the height of their careers, the comedians who pioneered Stand Up Comedy have shifted to other fields. This study also demonstrates that Stand Up Comedy has spawned a new generation of comedians who will continue the fantastic work of senior comedians.